A systematic review of clinical practice guidelines on uncomplicated birth. (14th January 2020) - Zhao, Y; Lu, H; Zang, Y; Li, X
Abstract : Background: Clinical practice guidelines on uncomplicated birth provide clinical practice guidance and help to reduce unnecessary, non‐evidence‐based and potentially harmful intrapartum care practices. Little is known about the trustworthiness and consistency of these guidelines. Objectives: To appraise guidelines relevant to uncomplicated birth, and summarise consensus and non‐consensus recommendations. Search strategy: Eight literature databases and the websites of guideline development institutions and organisations of obstetricians, gynaecologists and midwives were searched from January 2008 to October 2018. Selection criteria: Guidelines that: reported in Chinese or English; labelled guideline, or recommendation, or consensus, or practice parameter, or position paper/stand; with uncomplicated birth being the primary objectives or comprised chapter(s); and were the most recently published or updated versions. Data collection and analysis: Two reviewers independently assessed guideline quality using the AGREE II instrument, and synthesised consensus and non‐consensus recommendations using the content analysis approach. Main results: Eleven guidelines met the inclusion criteria. The WHO and NICE guidelines were deemed to have the highest methodological quality. Twenty‐three discrepant recommendations and 39 groups of unanimous recommendations (containing 113 individual ones) were identified, among which 14 recommendations including eating and drinking as desired, prophylactic uterotonics, routine amniotomy and episiotomy were included in five or more guidelines. Perineal massage, uterine massage, active or expectant management at the third stage and use of hands‐on or hands‐poised technique were identified as the main discrepant recommendations. Conclusions: Two guidelines with higher methodological quality and key clinical guideline recommendations, including both consensus and non‐consensus ones, on uncomplicated birth were identified. Tweetable abstract: Clinical guidelines of uncomplicated birth agree and disagree on several key recommendations. Tweetable abstract: Clinical guidelines of uncomplicated birth agree and disagree on several key recommendations.